Pemberian Jus Buah Bit ( Beta Vulgaris L) Terhadap Penurunan Tekanan Darah Pada Pasien Hipertensi - Putri Adira; Indrawati Indrawati; Erma Kasumayanti (Excellent Health Journal, 2025)
Hypertension can cause damage to the heart, blood vessels, kidneys, lungs, and motor and sensory nervous systems, and can even affect a person's mental health. Approximately 1 in 5 sufferers with hypertension are at high risk of losing their lives. The purpose of this scientific research is to provide nursing care to Mr. S in an effort to lower blood pressure in hypertensive patients through the administration of beetroot juice (beta vulgaris L) in Kualu Nenas Village. The subject of this research is Mr. S. The research took place from April 27 to 30, 2025. The data collection methods used include in-depth interviews with Mr. S and his family members, direct observation, physical examination, and blood pressure measurement. The tools used in data collection include family nursing assessment sheets and blood pressure measuring tools. The results of blood pressure measurements obtained during the assessment were 175/100 mmHg, with a pulse of 88 beats per minute, a respiratory rate of 20 times per minute, and a body temperature of 36.6℃. Mr. S's height is 160 cm and his weight is 70 kg. The action taken by the researcher regarding the problem faced by Mr. S was to provide beetroot juice therapy (beta vulgaris L). This research applied a case study design with a qualitative descriptive approach and identified the main nursing problems based on the results of the direct study. The case analysis showed a decrease in blood pressure after the patient consumed beetroot juice twice a day. It is hoped that the patient can continue to consume beetroot juice when blood pressure increases.